“El fortín del orden”. - Rodriguez Agüero, Laura (Universidad Nacional del Litoral, 2020)
This work aims to study the role played by the provincial police in the deployment of repressive actions during the last military dictatorship (and the previous years). In this direction, we propose, first of all, to analyze the role played by the Mendoza police under the command of Vice Commodore Julio César Santuccione in the development of legal and illegal repressive actions between 1975 and 1976, identifying breaks and continuities. Secondly, we will analyze the centrality of Department of Information 2 (D2) and its operation from a diachronic approach taking into account gender and class perspectives. This work will be carried out from oral sources, testimonies and judicial documents obtained in the successive trials against humanity.